Transitioning Towards More Equality? Wealth Gender Differences and the Changing Role of Explanatory Factors over Time - Eva Sierminska; Daniela Piazzalunga; Markus M. Grabka (Institute of Labor Economics (IZA), 2019)
The objective of the study is to investigate the changing role of explanatory factors of wealth and the gender wealth gap in Germany over the period 2002-2012 using individual level microdata from the German Socio-Economic Panel. The authors apply distributional decomposition methods and focus on the role of changes in labor supply, permanent income, portfolio composition, and marital status in this process. Results show that real mean wealth levels for the working age population have been decreasing for both women and men since 2002 and that the wealth gap has decreased by 13.5% to 30.700â,¬. The growing labor market participation of women and the resulting occupational structure has a positive effect on women's wealth accumulation. In comparison to previous analyses, the authors use the panel dimension of the data and find that the role of permanent income is decreasing due to a reduction in the gender difference in permanent income and in gender differences in its returns.
Keywords: D31; D13; 330; decomposition analysis; SOEP; gender; wealth differences